Effect of Pr3+doping on key properties of CdO thin films deposited by spray pyrolysis using perfume atomizer. (July 2018) - Ravikumar, M.; Chandramohan, R.; Kumar, K. Deva Arun; Valanarasu, S.; Kathalingam, A.; Ganesh, V.; Shkir, Mohd.; AlFaify, S.; Algarni, H.
Abstract: High quality Cadmium oxide thin films doped with Praseodymium (Pr) were prepared using perfume atomizer based spray pyrolysis technique at substrate temperature near 350 °C. Structural analysis of films was examined by XRD and confirmed that the films are cubic in structure. All un-doped and doped films were good crystalline in nature with smooth and flat surface without significant modifications owed to doping. Optical transmittances of doped films was decrease in the visible and IR range with increasing Pr doping concentration. Band gap widened from 2.42 to 2.20 eV when doped with Pr from 0 to 5 at. %. In addition, the photoluminescence property of the films was also observed. Further, the electrical studies were performed on pure and doped samples Viz., the electrical resistivity, carrier concentration (ρ) and Hall mobility (μ). It confirmed that the deposited films has good structural environments in terms of grain size, absolute stress correspond and low resistivity. Current-voltage measurements on the nanostructured Al/Pr-nCdO/p-Si/Al device showed a non-linear electric characteristics indicating diode like behavior. Graphical abstract: Highlights: Pr doped CdO films were fabricated by spray pyrolysis using perfume atomizer. Energy band gap was found to be widened from 2.21 to 2.31 by Pr doping in CdO. Resistivity is decreased from 2.7 × 10 −3 to 0.05 × 10 −3 Ωcm due to Pr concentrations. Values of ρ & n are found to 11.8 × 10 20 cm −3 and 25 cm 2 /V for 5% Pr doped CdO films. Responsivity of n-CdO/p-Si hybrid heterojunction diode is found to be 410 mA/W.